Growth and microbiology of nonmedicated, segregated, early-weaned pigs - Chengappa, M. M.; Vorhies, M.W.; Dritz, Steven S.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy pigs, 7 to 10 d of age, were randomly selected by litter of origin from a commercial farm in Northeast Kansas to compare the growth and microbiology of nonmedicated, segregated, early-weaned pigs to controls raised at the farm of origin. After weaning, both groups were fed a similar nutritional programs consisting of dry diets. No antimicrobial drugs were administered to the pigs except for a feed grade antimicrobial (carbadox) from weaning to 50 lb. Pigs were monitored for 12 weeks. Individual pigs weights, nasal swabs, and serum samples were collected on d 0 and then every 14 d thereafter for a total of 7 collections. Four pigs were necropsied at the initiation of the study (d 0). In addition, four pigs were randomly selected at each collection period from each group for necropsy and collection of tissues for bacterial culture. The segregated earlyweaned pigs were able to reach an accelerated phase of growth before the controls. On d 14, 28, 42, 56, and 70 of the experiment, segregated early-weaned pigs were 21, 82, 90, 54, and 52% heavier than control pigs, respectively. A low percentage of pigs were infected with Pasteurella multocida at 7 to 10 d of age, which corresponds to d 0 of the experiment. The principal time of transmission of P. multocida infection was in the immediate postweaning period. The rate of isolation of P. multocida then declined from d 14 to d 84 of the experiment in both groups of nonmedicated pigs. This response must be kept in mind when evaluating the efficacy of antibiotic protocols. Appropriate nonmedicated controls must also be evaluated. The maximum difference in rate of isolation of P. multocida from nasal swabs and tissues between the early and control groups occurred on d 28 and d 42 of the experiment. This corresponds to the two collection days when segregated early-weaned pigs were 82% and 90% heavier than control pigs raised on-site. The only Pasteurella multocida isolates capable of producing toxin were detected on d 14 in the control group. Pasteurella multocida toxin has also been shown to have deleterious effects on systemic organs and immune response. The rates of Bordetella bronchiseptica isolation were similar between control and segregated early-weaned groups. However, B. bronchiseptica isolates were recovered from any tissues of any pigs necropsied. Antibiotic regimens targeted at this organism would appear unwarranted in a commercial production setting. Haemophilus parasuis and Streptococcus suis were present in both groups of pigs at 7 to 10 d of age. However, as indicated by the excellent growth performance achieved in the presence of H. parasuis colonization of the nasal cavity, elimination of this organism probably is not necessary to achieve excellent growth levels. More studies need to be undertaken to understand the mode of transmission and epidemiology of Streptococcus suis infection. Mycoplasma hyopneumoniae apparently was eliminated without medication by moving pigs to an isolated site. Mycoplasma hyopneumoniae could be detected only in the control group. Data from this experiment also suggest that weaning pigs at 14 to 17 d could prevent vertical transmission of Actinobacillus pleuropneumonia. The growth and microbiology of nonmedicated, segregated, early-weaned pigs must be considered when developing cost-effective and efficacious medication protocols for application of segregated early weaning in the commercial swine industry.
Keywords: Swine; Pigs; Growth; Microbiology